Chemical structure and optical signatures of nitrogen acceptors in MgZnO. Issue 19 (14th April 2020) - Zakria, M.; Bove, P.; Rogers, D. J.; Teherani, F. H.; Sandana, E. V.; Phillips, M. R.; Ton-That, C.
Abstract : Nitrogen can be incorporated into MgZnO using low-temperature deposition. Donor–acceptor pair emission from N-doped MgZnO is attributed to molecular N2 . Abstract : The chemical and optical properties of wurtzite N-doped MgZnO epilayers with 16 at% Mg were grown by pulsed laser deposition and investigated using Near Edge X-ray Absorption Fine Structure (NEXAFS) and photoluminescence (PL) spectroscopy. When grown under nitrogen ambient the epilayers were an order of magnitude more resistive and displayed significantly different optical signatures compared with epilayers grown using similar conditions under oxygen or vacuum atmospheres. NEXAFS reveals that nitrogen in MgZnO:N exists in multiple chemical states with molecular N2 and substitutional N at an O site (NO ) being the dominant species. The MgZnO:N epilayer exhibited a distinct PL peak centered at 3.45 eV, which possessed an activation energy of 48 meV and showed a blue shift with increasing excitation power density. This PL emission in the MgZnO:N epilayer was attributed to a shallow donor – deep acceptor pair recombination mechanism, where the compensating deep acceptor was most likely molecular N2 at a Zn site. The results of this study offer the possibility of enhancing acceptor incorporation in oxides as well as for tuning their electrical and optical properties.